2022
DOI: 10.3389/fimmu.2022.1015409
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and insights into the structural characteristics of drug-induced autoimmune diseases

Abstract: The incidence and complexity of drug-induced autoimmune diseases (DIAD) have been on the rise in recent years, which may lead to serious or fatal consequences. Besides, many environmental and industrial chemicals can also cause DIAD. However, there are few effective approaches to estimate the DIAD potential of drugs and other chemicals currently, and the structural characteristics and mechanism of action of DIAD compounds have not been clarified. In this study, we developed the in silico models for chemical DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…There is more that could be done to refine our approach and improve the accuracy of its prediction. For example, as noted previously, other groups have had success with using structural data to predict DIA (Wu et al, 2021;Guo et al, 2022). It may therefore be possible to combine transcriptional with structural data.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There is more that could be done to refine our approach and improve the accuracy of its prediction. For example, as noted previously, other groups have had success with using structural data to predict DIA (Wu et al, 2021;Guo et al, 2022). It may therefore be possible to combine transcriptional with structural data.…”
Section: Discussionmentioning
confidence: 92%
“…One such model demonstrated that drugs containing benzene with a nitrogen containing substituent were significantly associated with a higher risk of inducing autoimmunity (Wu et al, 2021). Others have compared different machine learning methods and different molecular fingerprint packages to predict DIA using molecular properties and structural alerts (Guo et al, 2022). Although helpful, chemical structure alone may not be sufficient to determine the risk of DIA in patients, and whilst structural analysis of chemical compounds is highly sensitive, it has the potential for generating false positives (Stepan et al, 2011).…”
Section: Previous Attempts To Predict Diamentioning
confidence: 99%
“…In recent years, mitochondria-related research has been concerned with drug discovery and ecotoxicology. , In vivo tests are often difficult to detect mitochondrial toxicity due to poor responses in laboratory animals, and they always manifest as organ toxicity, which cannot be easily determined as mitochondrial toxicity. In vitro studies seem more suitable, but they also require specialized equipment and cost a lot. , In silico methods, especially quantitative structure–activity relationship (QSAR) with machine learning and deep learning tools, can be used to develop artificial intelligence (AI) models by synthesizing data from in vivo and in vitro experiments to better understand and predict the chemical mitochondrial toxicity. There were several different in silico models developed for the assessment of mitochondrial toxicity of pharmaceuticals and environmental chemicals . Zhang et al developed the support vector machine (SVM) model of mitochondrial toxicity using a dataset containing 288 small molecular drugs.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The computational toxicology tools can be used to prioritize chemical tests and further provide some mechanistic insights. 18,19 It is of great interest to develop computational tools to assess chemical neurotoxicity potential. The machine learning modeling was widely used to estimate the toxicity potential of chemical substances.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Computational toxicology is rapidly evolving with the proliferation of commercial databases and advances in modern computational tools for the analysis of large data sets, since it can integrate a variety of information and data to complement and extend traditional experimental toxicology research methods and encompasses multiple disciplines. , The computational toxicology tools can be used to prioritize chemical tests and further provide some mechanistic insights. , …”
Section: Introductionmentioning
confidence: 99%